2023
DOI: 10.1187/cbe.22-05-0088
|View full text |Cite
|
Sign up to set email alerts
|

Costs and Benefits of Undergraduates Revealing Depression to Online Science Instructors

Abstract: This study of 1179 undergraduates with depression examined whether students revealed their depression to their online science instructors and the reasoning behind their decisions. Few students revealed their depression, but perceived that if they did, they would benefit by receiving accommodations but risk instructor judgment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…Prior research from our group has found that college science students are often reluctant to reveal their depression in science learning environments, but if learning environments are inclusive and welcoming, then students are more comfortable revealing this important aspect of themselves ( Cooper et al. , 2020b ; Busch et al. , 2023 ).…”
Section: Resultsmentioning
confidence: 99%
“…Prior research from our group has found that college science students are often reluctant to reveal their depression in science learning environments, but if learning environments are inclusive and welcoming, then students are more comfortable revealing this important aspect of themselves ( Cooper et al. , 2020b ; Busch et al. , 2023 ).…”
Section: Resultsmentioning
confidence: 99%
“…Depression is characterized by a pervasive feeling of sadness, anhedonia, difficulty concentrating or making decisions, feelings of worthlessness or excessive guilt, recurrent thoughts of death or self-harm, changes in sleep patterns or appetite, restlessness or slow movements, and a persistent feeling of tiredness or lack of energy [ 10 , 11 ]. It is one of the most common manifestations of psychiatric pathologies and is closely associated with significant disability, impaired health-related quality of life, and increased mortality [ 12 ].…”
Section: Introductionmentioning
confidence: 99%